Alterations in DNA Damage Repair Genes Before and After Neoadjuvant Cisplatin-based Chemotherapy in Muscle-invasive Bladder Cancer - Ursula Lemberger; Büsra Ernhofer; Sigurd Krieger; Andreas Bruchbacher; André Oszwald; Ekaterina Laukhtina; Andrea Haitl; Melanie R. Hassler; Bernhard Englinger; Eva Compérat; Shahrokh F. Shariat (European Urology Open Science)
Background and objective: The role of genetic variants in response to systemic therapy in muscle-invasive bladder cancer (MIBC) is still elusive. We assessed variations in genes involved in DNA damage repair (DDR) before and after cisplatin-based neoadjuvant chemotherapy (NAC) and correlation of alteration patterns with DNA damage and response to therapy. Methods: Matched tissue from 46 patients with MIBC was investigated via Ion Torrent–based next-generation sequencing using a self-designed panel of 30 DDR genes. Phosphorylation of γ-histone 2A.X (H2AX) was analyzed via immunohistochemistry to evaluate DNA damage. Genetic variants were analyzed along with clinical data and quantitative phospho-H2AX data using the Kaplan-Meier method, Cox regression analysis, and factor analysis of mixed data. Key findings and limitations: Twenty-five patients (54%) had a response (<pT2 pN0 cM0) to NAC. Responders had more somatic DDR gene variants in preNAC (53 vs 11; p < 0.001) and postNAC (51 vs 9; p = 0.038) tumor tissue in comparison to nonresponders, as well as significantly greater phosphorylation of H2AX after NAC. ERCC2 was significantly co-mutated with REV3L among responders. Owing to the small cohort, no specific mutation was significantly positively associated with therapy response. However, accumulation of CDK12, NBN, MSH3, MLH1, ATR, BRCA1, BRCA2, REVL3L, and SLX4 variants was observed for responders. Conclusions and clinical implications: Patients with MIBC who responded to cisplatin-based NAC had more somatic DDR gene variants than nonresponders. Moreover, responders exhibited significantly greater DNA damage after NAC. Patient summary: Patients with muscle-invasive bladder cancer who have mutations in genes that are involved in repair of DNA damage are more likely to respond to cisplatin-based chemotherapy. Testing to identify these gene mutations could help in selecting the patients who are most likely to benefit from this treatment.